COMPARATIVE ANALYSIS OF VINCENTY AND GEODESIC METHOD APPROACHES IN MEASURING THE DISTANCE BETWEEN SUBDISTRICT OFFICES IN SALATIGA CITY - Windarni, Vikky Aprelia; Setiawan, Adi (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
Salatiga city has four subdistrict offices, namely Argomulyo Subdistrict, Sidorejo Subdistrict, Sidomukti Subdistrict and Tingkir Subdistrict. In this study, a comparative analysis of the distance between subdistrict offices in Salatiga city was conducted using the Vincenty method and Geodesic method with distance obtained from Google Maps. The data is the geographical coordinates of the Earth's surface (latitude and longitude) obtained from Google Earth. The results showed that both Vincenty and Geodesic methods compared with Google Maps calculation results between 95% -105%, so it can be said to be good. The geodesic method gives relatively better results than the Vincenty method because it has an average percentage of 99.58 %. In comparison, the Vincenty method has an average percentage of 99.48 %. However, the results obtained still use relatively less data.